On Subcartesian Spaces Leibniz' Rule Implies the Chain Rule. Issue 2 (7th June 2020) - Cushman, Richard; Śniatycki, Jędrzej
Abstract: We show that derivations of the differential structure of a subcartesian space satisfy the chain rule and have maximal integral curves.